Projek Penguatan Profil Pelajar Pancasila (P5) untuk Membentuk Gotong Royong Siswa di SMAN 1 Garum - Rohmah, Fitrotin Nur; Baihaqi, M Iqbal; Santoso, Minto (Universitas PGRI Semarang, 2024)
This research aims to provide a presentation on the results of the implementation of the Pancasila Student Profile Strengthening Project (P5) in forming a mutual cooperation attitude of students at SMA Negeri 1 Garum. The Pancasila Student Profile Strengthening Project (P5) is a project-based learning model that produces products. These project activities provide students with a meaningful and student-focused experience. This study uses a type of descriptive qualitative research. This research was carried out at SMA Negeri 1 Garum from April to May 2024. The subjects of this study are curriculum waka, classroom facilitator teachers and students of grades X and XI. The data collection techniques used are observation, interviews, open questionnaires and documentation. The data validity technique uses source triangulation and triangulation techniques. It is analyzed by reducing data, digesting data, and drawing conclusions. The results of this study show that the implementation of the Pancasila student profile strengthening project has an impact on shaping students' mutual cooperation attitudes with the ability to collaborate, care, and share.